Penerapan Metode Pembelajaran Contextual Teaching and Learning (CTL) untuk Meningkatkan Kemampuan Menulis Siswa Kelas V SD GMIT Oepura pada Teks Prosedur - Nenoliu, Rona; Djuli, Labu; Koro, Maxsel (Lembaga Yasin AlSys, 2025)
This study aims to improve the ability to write procedural texts in class V of GMIT Oepura Elementary School through the application of the Contextual Teaching and Learning (CTL) Method. This type of research is Classroom Action Research (CAR). The research procedure was carried out with pre-cycle activities then continued with cycles I and II on 22 research subjects. The data collection techniques used were interview techniques, observation, test techniques and documentation. The results of the cycle I study showed that the activities of educators and students obtained an average value of 61,36 and 51,25 so that both were classified as sufficient and lacking criteria. Furthermore, in the second cycle of learning, the activities of educators in the classroom had increased, namely the value of the educator's observation of 84,09 with the criteria of Good (B) and the average test results of students were 87.39% with the criteria of Very Good (SB). In cycle II, educators tried to improve previous learning so that the completeness of students in cycle II increased with the percentage of completeness of student learning outcomes reaching 100%, it can be concluded that using the Contextual Teaching and Learning (CTL) learning method can improve students' writing skills.